Cheating Intention of Students Based on Theory of Planned Behavior - Dewanti, Patriani Wahyu; Purnama, Ida Ayu; Siregar, Merinda NN; Sukirno, Sukirno (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
The aim of this research is to examine empirically the form of Theory of Planned Behavior in predicting the intention of cheating in accounting students. The samples taken in this research were 426 accounting students. The research employed a mixed-method, with a regression analysis for the quantitative and an analytic induction for the qualitative method. The results of this research found that of all the variables tested, subjective norms were the variables that had the greatest influence on the intention to cheat accounting students, while the moral obligation variable had the second largest influence and perceived behavioral control as the third predictor on the intention to cheat accounting students. The implication of the research is that the main influence of the academic fraud is subjective norms. Keywords: Theory of planned behavior, subjective norms, academic integrity.